The not so innocent bystander: an unusual cause of progressive breathlessness. Issue 8 (21st January 2021) - Lyon, Max; Whiteway, Alastair; Darby, Michael; Bhatt, Nidhi; Barratt, Shaney L
Abstract : This case report discusses a 76-year-old man who presented with symptomatic diffuse alveolar-septal and tracheobronchial amyloidosis with a low-grade monoclonal gammopathy. This patient had a combination of both symptomatic diffuse alveolar-septal interstitial disease and tracheobronchial amyloidosis, features that contradict the widely accepted presentations seen in this disease. First, tracheobronchial amyloidosis has been documented as localised disease without systemic involvement. Second, diffuse alveolar-septal interstitial disease is rarely identified with clinical symptoms unless there is significant cardiac involvement. This case highlights a number learning points in the diagnosis and management of systemic amyloid light chain amyloidosis;(1) There is a need for a high index of suspicion for diagnosis due to the potential subtlety of a plasma cell clone underlying AL amyloidosis, requiring serum-free light chain assays to increase sensitivity; (2) Haematological response and recovery of organ dysfunction are not a linear relationship due to the slower reversal of amyloid deposition; therefore, ongoing monitoring is required to identify those in need of repeated therapy. However, haematological response is a marker of overall survival and (3) Multisystem assessment and multidisciplinary collaboration are critical in optimising the care of patients with systemic AL amyloidosis.